2010
DOI: 10.1111/j.1540-6520.2009.00356.x
|View full text |Cite
|
Sign up to set email alerts
|

Syndication of Venture Capital Investment: The Art of Resource Pooling

Abstract: This article explores the rationale of syndications of institutional venture capital investors when they fund start-ups. There is an implicit labor division between institutional venture capital investors in which pure venture capital firms are in charge of converting investment uncertainty into risk by funding the seed stage of start-ups. The other investors invest in the following stages to sustain the start-ups' development. Relationships between investors are also handled following informal rules. Exchange… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 50 publications
(69 reference statements)
1
35
0
4
Order By: Relevance
“…This also highlights the normative nature of the social investment market as such personal characteristics are also important in mainstream investment perceptions of investment readiness (Mason and Harrison, 2001;Wilson et al, 2007). This finding also offers support to prior research that suggested that information asymmetry was prevalent in the social investment market (Evenett and Richter, 2011), as subjective 'gut-feeling' evaluations of entrepreneurs traits are symptomatic of markets that lack clear information or metrics (Jankowicz and Hisrich, 1987;Ramón et al, 2007;Ferrary, 2010).…”
Section: "I Think the Main Barrier Is That A Lot Of Voluntary Social supporting
confidence: 74%
See 1 more Smart Citation
“…This also highlights the normative nature of the social investment market as such personal characteristics are also important in mainstream investment perceptions of investment readiness (Mason and Harrison, 2001;Wilson et al, 2007). This finding also offers support to prior research that suggested that information asymmetry was prevalent in the social investment market (Evenett and Richter, 2011), as subjective 'gut-feeling' evaluations of entrepreneurs traits are symptomatic of markets that lack clear information or metrics (Jankowicz and Hisrich, 1987;Ramón et al, 2007;Ferrary, 2010).…”
Section: "I Think the Main Barrier Is That A Lot Of Voluntary Social supporting
confidence: 74%
“…This has also been evidenced as taking place in the equity investment sector, with the evaluation of 'soft data' and the use of intuition forming an integral part of the venture capitalist investor's due-diligence process (Zacharakis and Shepherd, 2001). Often intuitive decision-making processes are a symbol of a lack of clear information in a market, as investors have to rely on their 'gut reaction' (Jankowicz and Hisrich, 1987), particularly when funding start-up or early-phase businesses (Ramón et al, 2007;Ferrary, 2010). Indeed, this last point relating to 'gut reaction assessments' has also been shown by prior research to take place in venture capital assessments of social entrepreneurs (Achleitner et al, 2012).…”
Section: Investment Readinessmentioning
confidence: 92%
“…Au-delà de l'apport en capital, les investissements doivent être appréhendés comme une forme de détournement du contrat pour permettre la création d'un lien social vecteur de diffusion de connaissances et de ressources (Ferrary, 2010 …”
Section: La Porosité Organisationnelle Du Dispositif Intrapreneurialunclassified
“…The VC syndicates similarly provide value-added services, while the syndicating VC firms can further pool financial and nonfinancial resources and enhance the ventures' performance (Lockett & Wright, 2001;Ferrary, 2010;Hopp & Rieder, 2011). Furthermore, the syndication activities take the VC firms beyond arm-length transactions to a network of relationships over time and space.…”
Section: Syndication Decisionmentioning
confidence: 99%